2000
DOI: 10.1093/ps/79.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meat temperature on proteins, texture, and cook loss for ground chicken breast patties

Abstract: Soluble proteins, myofibrillar proteins, collagen, texture, and cook loss were evaluated at different meat temperatures by heating ground and formed chicken breast meat in brass containers in a water bath to temperatures of 40, 50, 60, 70, or 80 C. The soluble proteins decreased by approximately 90% as meat temperature increased from 23 to 80 C. The myofibrillar protein subunits of molecular weight greater than 43 kDa decreased with increasing temperature from 23 to 80 C as analyzed via SDS-PAGE. Amount of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
86
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 37 publications
16
86
1
3
Order By: Relevance
“…The small differences observed with marinated meat can be associated with lower marinade yield rather than to a direct effect of the wooden breast abnormality. High amounts of liquid losses during cooking are usually associated with increased toughness of meat (Murphy and Marks, 2000). In a recent study, it was also found that inclusion of wooden breasts to some extent in sausages and nuggets increased the shear force and binding strength (Puolanne and Ruusunen, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The small differences observed with marinated meat can be associated with lower marinade yield rather than to a direct effect of the wooden breast abnormality. High amounts of liquid losses during cooking are usually associated with increased toughness of meat (Murphy and Marks, 2000). In a recent study, it was also found that inclusion of wooden breasts to some extent in sausages and nuggets increased the shear force and binding strength (Puolanne and Ruusunen, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The meat was cooked at a constant temperature using pre-heated water bath (Memmert, WNB 14; GMbH + Co. KH, D-91107 Schwabach, Germany) to the internal temperature of 80 °C for 30 min for the maximum water loss expected (Murphy & Marks, 2000). After cooking meat samples were cooled in water bath using cold water to the internal temperature of 20 °C, then water blotted or purged until sample became dry.…”
Section: Cooking Loss %mentioning
confidence: 99%
“…Most of the study reported on the changes of soluble sarcoplasmic reticulum protein, including changes in activity and molecular mobility (Murphy and Marks, 2000;Unda. et al, 1990).…”
Section: Discussionmentioning
confidence: 99%